2015
DOI: 10.3892/etm.2015.2364
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and musculoskeletal injuries in professional football players

Abstract: Abstract. The aim of the present study was to investigate the association between vitamin D receptor (VDR) gene polymorphisms and musculoskeletal injury (MI) in elite football players. In total, 54 male professional football players were recruited from an official Italian professional championship team between 2009 and 2013. The cohort was genotyped for the ApaI, BsmI and FokI polymorphisms and MI data were collected over four football seasons. No significant differences were identified among the genotypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
0
23
0
2
Order By: Relevance
“…Similarly, a study in 80 Italian white male gymnasts participating at international competitions found no relationship between the VDR -FokI polymorphism and athletic performance [ 41 ]. In addition, 2 studies by Massidda and colleagues in male Italian soccer players found no correlation of VDR -FokI polymorphism with athletic performance [ 42 ], and no association with incidence or severity of musculoskeletal injury [ 43 ]. A study by Nakamura and colleagues [ 44 ] in 44 Japanese male competitive athletes of various sport disciplines found frequencies of FF of 50.0, and Ff 47.7%; FF carries when compared to Ff carriers had 7.7% greater lumbar spine bone mineral content (BMC) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in 80 Italian white male gymnasts participating at international competitions found no relationship between the VDR -FokI polymorphism and athletic performance [ 41 ]. In addition, 2 studies by Massidda and colleagues in male Italian soccer players found no correlation of VDR -FokI polymorphism with athletic performance [ 42 ], and no association with incidence or severity of musculoskeletal injury [ 43 ]. A study by Nakamura and colleagues [ 44 ] in 44 Japanese male competitive athletes of various sport disciplines found frequencies of FF of 50.0, and Ff 47.7%; FF carries when compared to Ff carriers had 7.7% greater lumbar spine bone mineral content (BMC) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 Additional evidence is necessary to determine if vitamin D deficiency in elite football players (including collegiate athletes and National Football League players) affects the injury rate or athletic performance. 7,22,23,29 As mentioned before, Sun et al 35,36 found a correlation between vitamin D insufficiency and abnormal glucose homeostasis and changes in the hepatic lipid content in male collegiate football players. It has been reported that circulating 25(OH)D concentrations are negatively associated with fasting glucose concentration in young adults but also inversely correlated with the concentrations of 1hour glucose, 2-hour glucose after oral glucose tolerance, the increments of the glucose area under the curve, and the increments of the insulin area under the curve.…”
Section: Discussionmentioning
confidence: 77%
“…Methodological quality scores of the studies reviewed ranged from 11/15 to 15/15 on the McMaster scale. This quality was classed as high in one study (6%) 38 and excellent (94%) in the remaining 16 studies 22–37 . However, due to variability of methodologies and data analysis, a meta‐analysis was not possible.…”
Section: Resultsmentioning
confidence: 99%